Characterization and thermal study of organic extracts of urban solid waste - Almeida, Sonia de [UNESP]; Santos, Danilo Vitorino dos [UNESP]; Crespi, Marisa Spirandeli [UNESP]; Bernabé, G. [UNESP] (Springer Nature, 2014)
The urban residues put in landfill of the city of Sa˜o Carlos-SP, Brazil, in 2004 represent 58.7 % of decomposed organic material. The aim of this research was to characterize samples of urban solid waste and its organic extracts targeting the use of this residue without damaging the environment. The curves were obtained in a nitrogen atmosphere, a heating rate of 20 C min-1 , the temperature of 30–600 C. In the original sample after humidity loss, an event occured concerning the water constitution in the TG curve with an endothermic peak in the DTA curve. There was a presence of inorganic residue in the ashes. The organic matter present in the USR sample disposed in the landfill is constituted by several polarity, organics compounds from the degradation of lignin, cellulose, lipids, and other materials which thermal stabilities are distinct. The hexane extract features in its constitution two fatty acids, stearic and triacontano´ic, which are nonpolar compounds originating from bacteria present in the residue. The acids groups in extract hexane also were evidenced by X-ray diffraction and FTIR.
Keywords: urban solid waste; Thermal Study; organic extract